High-Wind Drag Coefficient Based on the Tropical Cyclone Simulated With the WRF-LES Framework - Jiang, Wenrui; Wu, Liguang; Liu, Qingyuan (Frontiers in Earth Science, 2021)
The numerical simulation of tropical cyclones (TCs) has been increasingly conducted using the Advanced Weather Research and Forecast (WRF) model with the large-eddy simulation (LES) technique. Given the importance of the boundary wind profile for the vertical exchange of horizontal momentum between the atmosphere and the ocean, the drag coefficient was evaluated in the numerical simulation with the WRF-LES framework at the finest horizontal grid spacing of 37 m. In the absence of the TC-ocean interaction, the drag coefficient derived from the simulated wind profile does not show the leveling off or decrease in the strong wind conditions. The drag coefficient increases with the increasing near-surface wind speed and agrees well with the extrapolation of the Large and Pond formula in the strong wind conditions. It is suggested that the boundary wind structure simulated with the LES technique may be unrealistic when the TC-ocean interaction is not fully considered.